Zbycie przez syndyka składników majątkowych wchodzących w skład masy upadłości — zagadnienia wybrane - Gil, Izabella (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The paper addresses the question of the consequences of legal acts of a trustee related to the disposal of assets of the bankrupt included in the bankruptcy estate and the impact of these acts on the course of the on-going civil proceedings instituted or carried out by the trustee or the bankrupt debtor. The trustee’s disposal of components making up the bankruptcy estate often entails a personaltransformation of parties in civil proceedings and evaluation of whether procedural succession has occurred effectively and also of the impact of these acts on the interruption of the course of limitation. This issue raises numerous questions of interpretation both in practice and in the subject literature. Due to the framework of the study, the paper shows only some of the issues related to the subject-matter of actions taken by the trustee in connection with the liquidation of the assets of the bankrupt debtor.
Keywords: syndyk; zbycie składników majątkowych; masa upadłości